Edema‐induced changes in tumor cell surviving fraction and tumor control probability in 131Cs permanent prostate brachytherapy implant patients. (7th January 2013) - Kehwar, Than S.; Jones, Heather A.; Huq, M. Saiful; Smith, Ryan P.
Abstract : The study is designed to investigate the effect of edema on the delivered dose, tumor cell surviving fraction (SF), and tumor control probability (TCP) in the patients of prostate cancer who underwent   131 Cs permanent seed implantation. The dose reduction, the SF, and the TCP for edematous prostate implants were calculated for 31 patients who underwent real‐time   131 Cs permanent seed implantation for edema half‐lives (EHL), ranging from 4 days to 34 days and for edema magnitudes ( M 0 ) varying from 5% to 60% of the actual prostate volume. A dose reduction in   131 Cs implants varied from 1.1% (for EHL = 4   days and M 0 = 5 % ) to 32.3% (for EHL = 34   days and M 0 = 60 % ). These are higher than the dose reduction in   125 I implants, which vary from 0.3% (for EHL = 4   days and M 0 = 5 % ) to 17.5% (for EHL = 34   days and M 0 = 60 % ). As EHL increased from 4 days to 34 days and edema magnitude increased from 5% to 60%, the natural logarithmic value of SF increased by 4.57 and the TCP decreased by 0.80. Edema induced increase in the SF and decrease in the TCP in   131 Cs seed implants, is significantly more pronounced in a combination of higher edema magnitude and larger edema half‐lives than for less edema magnitude and lower edema half‐lives, as compared for M 0 = 60 % and EHL = 34, and M 0 = 5 % and EHL = 4   days . PACS number: 87.53.Jw